2006
DOI: 10.1073/pnas.0608678103
|View full text |Cite
|
Sign up to set email alerts
|

Refolding of a paramyxovirus F protein from prefusion to postfusion conformations observed by liposome binding and electron microscopy

Abstract: For paramyxoviruses, two viral glycoproteins are key to the entry process: an attachment protein (HN, H, or G) and the fusion protein (F). The F protein folds to a metastable state that can be triggered to undergo large conformational rearrangements to a fusogenic intermediate and a more stable postfusion state. The triggering mechanism that controls paramyxovirus fusion has not been elucidated. To correlate the molecular structure of a soluble form of the prefusion F (PIV5 F-GCNt) with the biological function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
103
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 51 publications
(63 reference statements)
10
103
1
1
Order By: Relevance
“…It was shown by Yin et al (72,73) that appending the GCNt helix to the HRB of a truncated PIV5 sF construct yielded a prefusion structure in comparison to the structure for the non-GCNt-appended hPIV3 sF glycoprotein, which spontaneously folds to a postfusion configuration. In addition, it was demonstrated that the prefusion PIV5 sF GCNt could be activated and refolded to a postfusion conformation in vitro by heat and trypsin treatment (23). These earlier findings, together with the data described above, suggested that the HeV and NiV sF GCNt glycoproteins are also likely folded into a prefusion conformation, whereas the non-GCNt-appended forms are not and likely have a configuration similar to a postfusion configuration.…”
Section: Fig 6 Immunoreactivity Of Sf Glycoprotein Constructs With Nisupporting
confidence: 50%
See 3 more Smart Citations
“…It was shown by Yin et al (72,73) that appending the GCNt helix to the HRB of a truncated PIV5 sF construct yielded a prefusion structure in comparison to the structure for the non-GCNt-appended hPIV3 sF glycoprotein, which spontaneously folds to a postfusion configuration. In addition, it was demonstrated that the prefusion PIV5 sF GCNt could be activated and refolded to a postfusion conformation in vitro by heat and trypsin treatment (23). These earlier findings, together with the data described above, suggested that the HeV and NiV sF GCNt glycoproteins are also likely folded into a prefusion conformation, whereas the non-GCNt-appended forms are not and likely have a configuration similar to a postfusion configuration.…”
Section: Fig 6 Immunoreactivity Of Sf Glycoprotein Constructs With Nisupporting
confidence: 50%
“…Paramyxovirus F glycoproteins demonstrate a propensity to aggregate in solution or when extracted out of membranes, which may be the result of an exposed Fp (23,48). The alteration of hydrophobic residues within the Fp of RSV F yielded an sF construct with a reduced tendency to aggregate (48).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The F trypsin mutant meets these conditions, based on our F-protein coimmunoprecipitation data and the previous observation that MeV F trypsin is fully reactivatable by the addition of exogenous trypsin protease (38). Furthermore, uncleaved F trimers derived from the related paramyxovirus PIV5 were shown to remain competent in refolding into a postfusion conformation (19,52), confirming that no obvious structural constraints prevent the conformational rearrangement of F trypsin -containing trimers in a dominant-negative manner.…”
Section: Discussionmentioning
confidence: 64%